Pengaruh Inflasi, Ukuran Perusahaan dan Bagi Hasil terhadap Jumlah Deposito Mudharabah (Studi Empiris pada Bank Umum Syariah yang Terdaftar di Otoritas Jasa Keuangan pada Tahun 2018-2022) - Nur Abadi Siregar; Fina Fitriyana (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
This study aims to empirically test and prove the effect of inflation, company size and profit sharing on the amount of mudharabah deposits (Empirical Study on Islamic Commercial Banks Registered with the Financial Services Authority in 2028-2022). This study uses the dependent variable, namely the Amount of Mudharabah Deposits (Y) and the independent variables are Inflation (X1), Company Size (X2), and Profit Sharing (X3). This study uses the financial statements of Islamic commercial banks registered with the financial services authority in 2018-2022. The type of research used is quantitative, the type of data used is secondary data. The population in this study is Islamic Commercial Banks registered with the Financial Services Authority (OJK) in 2018-2022 consecutively. The sampling method in this study uses purposive sampling technique, there are 30 samples that will be used in this study. This study uses panel data regression analysis techniques for data management using Eveiws 12 Software. The results of this study indicate that inflation, company size and profit sharing simultaneously affect the amount of mudharabah deposits. Partially inflation and profit sharing do not affect the amount of mudharabah deposits, while Company Size affects the amount of mudharabah deposits.